Linguistic Landscape of the Town of Kovаčicа - Radić Bojanić, Biljana B.; Bovđiš, Tatjana J. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
In researching the linguistic landscape of Kovačica, we analyze the linguistic diversity of this multicultural town with a focus on both official and public inscriptions. The aim was to ascertain how minority language policies regulate public language use, as well as to examine whether one of the languages is more dominant than the other and whether a certain language is used for certain domains. The research corpus consisted of 152 photographs and accompanying notes taken during fieldwork. Through a detailed analysis of the corpus, we come to the conclusion that the linguistic landscape of the town of Kovačica is diverse and in accordance with the structure of the population and the languages that are in official use in the territory of the municipality of Kovačica. Regarding official inscriptions, we notice that Serbian, as the official and majority language in the Republic of Serbia, is more dominant than Slovak, except for some situations, for example street names and inscriptions on local historical monuments. On the other hand, the Romanian and Hungarian languages appear only on official signs as a feature of a multinational municipality in which four languages are in official use, which means that those two languages do not appear in other domains of the language landscape of Kovačica. In addition, English is becoming more prevalent in the official language landscape of Kovačica, especially in the tourist sector, which reflects the impact of globalization and the need to communicate with a wider international audience. When public written signs are concerned, our analysis shows the indisputable dominance of the Serbian language, which indicates a tendency towards monolingualism in the public space. In addition, there are occasional deviations in the spelling and correct use of both the Serbian and Slovak languages in the public space. Overall, the linguistic landscape of Kovačica reflects the town’s rich traditional culture and confirms that the official use of languages is in line with Serbian legislation, but the private sphere does indicate a gradual shift from multilingualism towards monolingualism.
Keywords: Kovačica; linguistic landscape; minority language policy; public signs; private signs